2019
DOI: 10.1149/2.0331902jes
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Morphological Change from Trenching to Pitting around Intermetallic Particles in AA1050 Aluminum

Abstract: The mechanism of trenching and pitting at intermetallic particles in AA1050 aluminum was investigated by open circuit potential measurements and microscopic polarization measurements, and the role played by the two types of intermetallic particles, Al-Fe and Al-Fe-Si, in this process was determined. Trenching was observed only around the Al-Fe-Si particles in the naturally aerated 0.1 M NaCl solution. Under the anodic polarization of AA1050 in naturally aerated 0.1 M NaCl, a crystallographic pit was initiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…As can be observed, the surface of the blank sample has been degraded by trenching of the intermetallic compounds. This finding is in good agreement with the previous work conducted to study the corrosion behavior of the aluminum alloy in the presence of intermetallic compounds [66][67][68] . The trenching attack is strengthened at prolonged exposure times.…”
Section: Resultssupporting
confidence: 93%
“…As can be observed, the surface of the blank sample has been degraded by trenching of the intermetallic compounds. This finding is in good agreement with the previous work conducted to study the corrosion behavior of the aluminum alloy in the presence of intermetallic compounds [66][67][68] . The trenching attack is strengthened at prolonged exposure times.…”
Section: Resultssupporting
confidence: 93%
“…Figure 3(c) confirmed that the Al-matrix was locally dissolved during the chromate treatment for 10 h. From micro-scale electrochemical measurements of AA1050, it was concluded that not all of the IMPs acted as initiation sites for pitting. 6,18) As shown in Fig. 3(c), also in this case, not all of the IMPs acted as A d v a n c e V i e w initiation sites for pitting.…”
Section: A D V a N C E V I E Wmentioning
confidence: 67%
“…The AA1050 used in this study was the same as that used in our previous study. 6,18) The specimens were annealed at 623 K for 1 h and slowly cooled in a furnace (the cooling rate was approximately 65 K h ¹1 ). The specimen surface was mechanically ground with SiC paper to 4000-grit and polished with diamond pastes (15, 6, 1, and 0.25 µm).…”
Section: Specimensmentioning
confidence: 99%
See 2 more Smart Citations